Natural Resource Policy Through Capability Approach: Case of Coal Mining and Palm Oil Industry in Indonesia - Sunaryo Sunaryo; Ika Karlina (Research Synergy Foundation, 2019)
This article can be seen as a ‘moral’ evaluation to the most important of natural resource sectors in Indonesia, namely the coal mining sector and palm oil plantations through the capability approach as formulated by Amartya Sen and Martha Nussbaum. These two sectors are important because they have a large contribution to state revenue, but unfortunately, at the same time, both also have a large contribution to the destruction of the environment, health and conflict in society, which are very important to support the quality of human life. Through this approach, I hold that for coal mining, even though it makes a large contribution to state revenue, the losses received related to the things that support the quality of human life are far greater. Therefore, for this sector, it is a good thing for the government to make a significant reduction by developing the mining process which is environmentally friendly and does not damage the quality of the healthy life of the people in the area. While the palm oil industry is basically not as bad as coal mining. But this industry has contributed to deforestation in Indonesia and damaged biodiversity. In this sector, the government also needs to look for the development of the palm oil plantation industry that is more environmentally friendly.